Preliminary Investigation of Spider Diversity in Kedarnath Wildlife Sanctuary, Uttarakhand, India - Quasin, S.; Uniyal, V. P. (Indian Forester, 2010)
A study was conducted to document spider diversity in Kedarnath Wildlife Sanctuary, Chamoli district, Uttarakhand. The Area is dense forest of Chir pine (Pinus roxburghii), Oak (Quercus semicarpifolia), Birch (Quercus leucotracophora) and Rhododendrons. A total of 64 species/morphospecies under 40 genus and 19 families were recorded. Majority of the spiders collected were web forming due to moist climate and dense vegetation.